Adaptive Governance of River Deltas Under Accelerating Environmental Change - Mandy Paauw; Murray Scown; Annisa Triyanti; Haomiao Du; Ahjond Garmestani (Utrecht Law Review, 2022)
Many deltas are increasingly threatened by environmental change, including climate change-induced sea-level rise, land subsidence and reduced sediment delivery. Dealing with these challenges is a pressing necessity because deltas are home to many people and are important centres for economic and agricultural development. Successfully adapting to climate change requires a social-ecological system (SES) perspective, emphasising that social and ecological components of deltas are intertwined. Various modes of governance have been suggested to deal with uncertainty associated with environmental change in SESs, such as adaptive governance. Adaptive governance underlines the need for governance systems to be flexible enough to adapt to variable degrees of uncertainty in SESs. In this paper, we analyse the Dutch Delta Programme (DDP) and the Mekong Delta Plan (MDP) to explore their strengths and limitations relating to nine principles for adaptive governance proposed by DeCaro and others. We evaluate the suitability of this framework for the Rhine and Mekong deltas and contribute to the current understanding of delta governance in light of climate change. Most of the principles outlined by DeCaro and others are present in the DDP and MDP. However, adaptive governance is context dependent. The Rhine and Mekong deltas display different obstacles to adaptive governance, some of which are not sufficiently emphasised in this academic adaptive governance framework. Instead of relying on one framework as a blueprint for adaptive governance, using principles from different frameworks depending on the case may be the best approach for addressing environmental challenges in deltas.